ACC/AATS/AHA/ASE/EACTS/HVS/SCA/SCAI/SCCT/SCMR/STS 2017 Appropriate use criteria for the treatment of patients with severe aortic stenosis: A report of the American College of Cardiology Appropriate Use Criteria Task Force, American Association for Thoracic Surgery, American Heart Association, American Society of Echocardiography, European Association for Cardio-Thoracic Surgery, Heart Valve Society, Society of Cardiovascular Anesthesiologists, Society for Cardiovascular Angiography and Interventions, Society of Cardiovascular Computed Tomography, Society for Cardiovascular Magnetic Resonance, and Society of Thoracic Surgeons. (15th January 2018) - ,; Bonow, Robert O; Brown, Alan S; Gillam, Linda D; Kapadia, Samir R; Kavinsky, Clifford J; Lindman, Brian R; Mack, Michael J; Thourani, Vinod H; ,; ,
Abstract: The American College of Cardiology collaborated with the American Association for Thoracic Surgery, American Heart Association, American Society of Echocardiography, European Association for Cardio-Thoracic Surgery, Heart Valve Society, Society of Cardiovascular Anesthesiologists, Society for Cardiovascular Angiography and Interventions, Society of Cardiovascular Computed Tomography, Society for Cardiovascular Magnetic Resonance, and Society of Thoracic Surgeons to develop and evaluate Appropriate Use Criteria (AUC) for the treatment of patients with severe aortic stenosis (AS). This is the first AUC to address the topic of AS and its treatment options, including surgical aortic valve replacement and transcatheter aortic valve replacement. A number of common patient scenarios experienced in daily practice were developed along with assumptions and definitions for those scenarios, which were all created using guidelines, clinical trial data and expert opinion in the field of AS. The '2014 AHA/ACC guideline for the management of patients with valvular heart disease: a report of the American College of Cardiology/American Heart Association Task Force on Practice Guidelines' [1 ] and its 2017 focused update paper [2 ] were used as the primary guiding references in developing these indications. The Writing Group identified 95 clinical scenarios based on patient symptoms and clinical presentation, and up to 6 potential treatment options for those patients. A separate, independent Rating Panel was asked to score each indication from 1 to 9, with 1–3 categorized as 'Rarely Appropriate', 4–6 as 'May Be Appropriate' and 7–9 as 'Appropriate'. After considering factors such as symptom status, left ventricular function, surgical risk, and the presence of concomitant coronary or other valve disease, the Rating Panel determined that either surgical aortic valve replacement or transcatheter aortic valve replacement is appropriate in most patients with symptomatic AS at intermediate or high surgical risk; however, situations commonly arise in clinical practice in which the indications for surgical aortic valve replacement or transcatheter aortic valve replacement are less clear, including situations in which one form of valve replacement would appear reasonable when the other is less so, as do other circumstances in which neither intervention is the suitable treatment option. The purpose of this AUC is to provide guidance to clinicians in the care of patients with severe AS by identifying the reasonable treatment and intervention options available based on the myriad clinical scenarios with which patients present. This AUC document also serves as an educational and quality improvement tool to identify patterns of care and reduce the number of rarely appropriate interventions in clinical practice.